MERIT SYSTEM: ASSESSMENT OF THE INDONESIAN GOVERNMENT WEBSITE - Muhammad Farhan HR; Suswanta Suswanta; Titin Purwaningsih; Wiyono Wiyono; Adibah Dhivani Gusmi (Sosiohumaniora, 2023)
This study aims to find information on the rating system on provincial government websites in Indonesia with a merit system. The method used is descriptive qualitative with two grammatical and systematic interpretation models. This research was conducted in six Indonesian provinces with excellent categories in implementing the merit system, including Central Java, West Java, Lampung, East Kalimantan, East Nusa Tenggara, and Central Sulawesi, which were assessed based on the value of the proportion of the system information aspect. The findings of this study show that Central Java and Lampung dominate the information system aspect in terms of personnel information systems, competency assessment centers, e-performance, and e-office, with a score of 100 from the other four provinces. This research has limited time to test abilities, adjusted to the results of old research and new research, especially in the areas of provincial governments in Indonesia. Disclosure of information system data in the Indonesian provincial government can be used as a basis for evaluating various subsequent information systems to realize transparency towards the public.